Organoleptic and Nutritional Quality of Carrot Skin Based Nuggets - Jananta, I Made Gede Trisna; Kartini, Luh Putu; Trisdayanti, Ni Putu Eka; Sunada, I Nyoman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the organoleptic and nutritional quality of carrot skin-based nuggets as an innovation in healthy food products. The organoleptic test involved 25 panelists to assess the taste, aroma, texture, and color of the nuggets. The results showed that carrot skin nuggets had good organoleptic quality with an average score of 85% for all tested variables. The nutritional content per 100 grams of nuggets includes balanced carbohydrates, proteins, fats, and calories, making them a healthy alternative compared to meat-based nuggets. This study opens up opportunities for diversification of plant-based food products and suggests further research to improve product quality and stability.